1998
DOI: 10.1074/jbc.273.32.20317
|View full text |Cite
|
Sign up to set email alerts
|

A Sequence within the Cytoplasmic Tail of GpIIb Independently Activates Platelet Aggregation and Thromboxane Synthesis

Abstract: All integrin ␣ subunits contain a highly conserved KXGFFKR motif in their cytoplasmic domains that plays a crucial role in the regulation of integrin affinity for their ligands. We show that a lipid-modified peptide corresponding to the cytoplasmic region, 989 -995, of the platelet integrin subunit glycoprotein GpIIb (␣IIb), palmitoyl-KVGFFKR (Ppep; 10 M), but not a similarly modified scrambled peptide (palmitoyl-FKFVRGK), can specifically induce platelet activation and aggregation equivalent to that of strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
76
2
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 34 publications
6
76
2
1
Order By: Relevance
“…However, the interpretation of such mutational data has remained conjectural, because the structure of the ␣ IIbcytoplasmic tail, as well as that of any of the ␣-subunits, is unknown. Recently, it has been shown that a lipid-modified peptide containing only the membrane-proximal region of ␣ IIb (K989-R995) can penetrate the platelet membrane and induce ␣ IIb ␤ 3 activation (8). This observation attests to the significance of the N-terminal region of the ␣ IIb -cytoplasmic tail in integrin activation and indicates that such peptides can adopt a functionally relevant conformation.…”
mentioning
confidence: 86%
“…However, the interpretation of such mutational data has remained conjectural, because the structure of the ␣ IIbcytoplasmic tail, as well as that of any of the ␣-subunits, is unknown. Recently, it has been shown that a lipid-modified peptide containing only the membrane-proximal region of ␣ IIb (K989-R995) can penetrate the platelet membrane and induce ␣ IIb ␤ 3 activation (8). This observation attests to the significance of the N-terminal region of the ␣ IIb -cytoplasmic tail in integrin activation and indicates that such peptides can adopt a functionally relevant conformation.…”
mentioning
confidence: 86%
“…Platelet Function-Gel-filtered platelets were prepared as previously described (1,4). Platelet aggregation assays were performed as described using 0.1 unit/ml thrombin or 10 M U46619, a thromboxane mimetic.…”
Section: Methodsmentioning
confidence: 99%
“…have previously established that the conserved amino acid sequence KVGFFKR, immediately adjacent to the transmembrane domain of the platelet ␣ IIb integrin subunit, plays a critical role in the regulation of integrin activation (4,42). To identify the protein-protein interactions responsible for this regulation, we synthesized a biotin-tagged peptide corresponding to this sequence and used it as a probe to identify high affinity protein interactions dependent on this motif.…”
Section: Kvgffkr-specific Binding Proteins Identified From High Densimentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence that cyclic peptides may have improved membrane permeability, compared with linear peptides, in cases where the cyclic peptide can internally satisfy its own hydrogen bonds. 15 Other approaches that have been used to successfully transport linear peptides inside cell membranes, such as palmytoylation, 16 may also be used with cyclic peptides.…”
Section: Introductionmentioning
confidence: 99%